2008
DOI: 10.1038/sj.bjc.6604463
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin 1 and Caveolin 2 are associated with breast cancer basal-like and triple-negative immunophenotype

Abstract: Caveolin-1 (CAV1) and caveolin 2 (CAV2) are the principal structural proteins of caveolae, sphingolipid and cholesterol-rich invaginations of the plasma membrane involved in vesicular trafficking and signal transduction. Over the recent years there has been controversy about their role in breast cancer and their suitability as markers of basal-like phenotype. Caveolin-1 and CAV2 protein expression was assessed on a tissue microarray containing 880 unselected invasive breast cancer cases, by means of immunohist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
93
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(110 citation statements)
references
References 52 publications
12
93
3
Order By: Relevance
“…It has been reported that the depletion of caveolin 1 decreased migration, polarization and focal adhesion in MDA-MB-231 cancer cells (basal-like phenotype) (10). This is consistent with another study, which demonstrated that caveolin 1 is highly associated with the breast cancer basal-like phenotype (11). In the present study, human breast cancer BT474 cells were used to analyze the role of caveolin 1 in BT474 cells.…”
Section: Introductionsupporting
confidence: 91%
“…It has been reported that the depletion of caveolin 1 decreased migration, polarization and focal adhesion in MDA-MB-231 cancer cells (basal-like phenotype) (10). This is consistent with another study, which demonstrated that caveolin 1 is highly associated with the breast cancer basal-like phenotype (11). In the present study, human breast cancer BT474 cells were used to analyze the role of caveolin 1 in BT474 cells.…”
Section: Introductionsupporting
confidence: 91%
“…Several studies reported that the E-cadherin/catenin complex and P-cadherin, of the cell-cell adhesion family, as well as Caveolin-1 and Id-1 genes are important regulators in the progression of human breast carcinomas. [6][7][8][9] In contrast, the role of the BRCA1 gene in cell invasion and motility of human breast cancer cells is not clear.…”
Section: © 2 0 0 8 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 99%
“…1A and B). Furthermore, we investigated the expression pattern of E-cadherin, P-cadherin, Caveolin-1 and Id-1, which are important regulators of cell motility and invasion, [6][7][8][9] in these cell lines.…”
Section: © 2 0 0 8 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 99%
“…Caveolae are enriched by sphingolipids and cholesterol (Zhu et al, 2008) and are directly involved in vesicular trafficking and signal transduction (Bouras et al, 2004;Chen et al, 2004;Elsheikh et al, 2008). Caveolae and caveolins have several functions including vesicular transport, cholesterol homeostasis, signal transduction, and tumor suppression (Bat'ová et al, 2003).…”
Section: Introductionmentioning
confidence: 99%